Memoires sur la Province d'Alsace
Manuscript volume (271 pages) by an unknown person subtitled "Description de la province d'Alsace dressée par M. l'intendant par ordre du Roy pour l'instruction de Monseigneur le Duc de Bourgogne..." Includes table of contents and chapters on churches and religion, trade, education, towns, chateaux, etc.
Collection material in French.
Keywords: Louis, -- Duke of Burgundy, Dauphin of France, -- 1682-1712.; Alsace (France) -- History; France -- History